(3OjhGf GdVYaGAs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg hdG Mhd hdG bhI EdG HGddg CeG HYO agPG OjhGf CSeGA GdVYaGA hGdeJQhcjf hNdb ef GdeLghdjf , hCfGS KbGJ ajge djf , Ydi JQJjH MQha GdeYLe s
(3BNQgG (B:s
(3HBNQg Pjd ddeDda Ydi gPG GdcJGH EdJbWg ef YOI JhGdja s
(3hbO QhO ChdgG Cfg cJGH GdeZfi ai GdVYaGA gh djS aEfg jNGda cJGH GdeZfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B64 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK s
Keywords: (3GdJGQjNs